2008
DOI: 10.1002/bit.21866
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as alternative co‐solvents for laccase: Study of enzyme activity and stability

Abstract: The activity and stability of commercial laccase (DeniLite base) in three different water soluble ionic liquids (ILs) (1-ethyl-3-methylimidazolium 2-(2-methoxyethoxy) ethylsulfate, [emim][[MDEGSO4], 1-ethyl-3-methylimidazolium ethylsulfate, [emim][EtSO4], and 1-ethyl-3-methylimidazolium methanesulfonate, [emim][MeSO3]) have been studied and compared to that in two organic solvents (acetonitrile and dimethyl sulfoxide). Initial enzyme activities were similar among the ILs if the same conditions were used. A hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 39 publications
7
63
0
3
Order By: Relevance
“…ILs like 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF 6 ) and 1-butyl-3-methylimidazolium tetrafluoroborate ([EMIM]BF 4 ) are known to be good alternatives to organic solvents in bioconversion 22 . The use of ILs in enzymatic reactions leads to remarkable improvements in thermostability, stereoselectivity, regioselectivity, and inhibition of side reactions [23][24][25][26][27] . ILs are also known as rather toxic solvents, since they can influence the stability and activity of enzyme through the anions' nucleophilic properties and hydrogen bonding [28][29][30] .The interaction formed by hydrogen bonds between anion and enzyme is very strong, which may cause a conformational change in the enzyme, thus affecting the enzyme activity.…”
Section: Effect Of Glycosylation Of β-Glucuronidase On Its Catalytic mentioning
confidence: 99%
“…ILs like 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF 6 ) and 1-butyl-3-methylimidazolium tetrafluoroborate ([EMIM]BF 4 ) are known to be good alternatives to organic solvents in bioconversion 22 . The use of ILs in enzymatic reactions leads to remarkable improvements in thermostability, stereoselectivity, regioselectivity, and inhibition of side reactions [23][24][25][26][27] . ILs are also known as rather toxic solvents, since they can influence the stability and activity of enzyme through the anions' nucleophilic properties and hydrogen bonding [28][29][30] .The interaction formed by hydrogen bonds between anion and enzyme is very strong, which may cause a conformational change in the enzyme, thus affecting the enzyme activity.…”
Section: Effect Of Glycosylation Of β-Glucuronidase On Its Catalytic mentioning
confidence: 99%
“…These first results of laccase kinetics suggested that the optimization of reaction conditions in ionic liquids may be necessary to obtain higher catalytic activities. Another work can be referred with laccase (Tavares et al, 2008) Enzymatic inhibition is another point that should be considered in kinetics. An inhibitor is any substance that reduces the reaction rate.…”
Section: Kineticsmentioning
confidence: 99%
“…In addition, there are difficulties associated with the use of LMS in conventional solvents. [28][29][30][31] In contrast to LMS, an electrolytic mediator system (EMS) (Figure 1b) could provide a promising and effective alternative for lignin depolymerisation. Instead of using a laccase to oxidise the mediator, the mediator can be oxidised electrochemically instead.…”
Section: Introductionmentioning
confidence: 99%